Atypical Posterior Reversible Encephalopathy Syndrome in a Postpartum Woman With Moyamoya Disease: A Case Report and Literature Review - Zou, Ning; Guo, Guixiang; Wan, Fangchao; Li, Xin (Frontiers in Neurology, 2021)
Background: Moyamoya disease is a rare cerebrovascular occlusive disease, which is characterized by stenosis and gradual occlusion of the internal carotid arteries, causing the progression of characteristic collateral vessels. To date, most studies investigating moyamoya disease have focused on medical implications, and the potential implications for neurocognitive and/or neuropsychiatric functioning were inconclusive. Case Presentation: we present a case of a 26-year-old Chinese postpartum woman who presented to the emergency department with a 19-h history of cognitive decline, vomiting, and convulsions. Blood pressure, heart rate, and respiration rate were 200/120 mmHg, 115 beats/minute, and 30 breaths/minute, respectively, on arrival. The Glasgow Coma Scale, modified RANKIN scale (mRS), and National Institute of Health stroke scale (NIHSS) scores were 3, 5, and 18, respectively. Moyamoya disease was diagnosed using cerebral angiography and digital subtraction angiography. The cognitive functions of orientation, use of language, ability to calculate, and memory significantly improved after 11 days of treatment (Glasgow Coma Scale: 15; mRS: 0; NIHSS: 0). Conclusions:This patient was diagnosed with reversible posterior leukoencephalopathy syndrome related to moyamoya disease. This case highlights that atypical posterior reversible encephalopathy syndrome can occur in patients with moyamoya disease, and should be considered for the differential diagnosis of cerebral infarcts and hemorrhage in a postpartum female.